Marketing Strategies to Increase Visits to Natural Tourism and Promote Local Products - Moh. Samsul Arifin; Heny Hidayati; Elizabeth; Faizatul Fajariah; Ita Nurcholifah (Indonesian Journal Economic Review (IJER), 2026)
Marketing strategies in the tourism business are essentially centered on creating, managing, and communicating a high-value experience, because the product being sold is not a physical object but rather memories and emotional satisfaction. In a highly competitive industry landscape, a tourism business must be able to build a strong and unique brand identity to be instantly recognizable amidst a sea of other destination options. The purpose of this research is to describe marketing strategies to increase visits to natural tourism and promote local products. This presentation is explained using a descriptive approach. This descriptive approach uses secondary data such as books, journals, and related sources. The research results show that developing a marketing strategy to increase visits to natural tourism while promoting local products is a smart move. The two have a symbiotic relationship: natural beauty attracts tourists, while unique local products provide authentic experiences that encourage them to spend more. A comprehensive marketing strategy that combines the promotion of natural tourism destinations and the economic empowerment of local products includes branding and positioning strategies, digital and content marketing, and on-site experiences.